Tourist Perspective Towards Glamping Accomodation In The Era Of Industry 4.0 And Society 5.0 - Ni Desak Made Santi Diwyarthi; I Wayan Adi Pratama; I Wayan Tagel Eddy (Jurnal Syntax Transformation, 2023)
Background, The Formulation Of The Problem Posed Is "How Is Glamping From The Perspective Of Domestic Tourists In The Industrial Era 4.0 And Society 5.0".This Study Aims To Determine The Opinion Of Domestic Tourists In Choosing Accommodation When Traveling In Balithe Research Is A Descriptive Research With Quantitative Research Approach To Answer The Questions Related To Glamping In The Tourist’s Perspectivesthis Study Shows The Results That Nomadic Tourism Synergizes With Educational Tourism, Digitalization And Events. The Combination Of These Various Factors Shows An Important Role In Driving The Destination Economy With The Homestay Business.The Data Analysis Technique Used In This Research Is Descriptive Analysis Technique, In Which The Research Results Are Described Descriptively Which Describes The Findings Obtained.Tourist Preferences For The Glamping Accommodation Business In Bali Prefer Glamping Which Is Promoted In An Attractive Way, With A Large Number Of Followers (A Large Number Of Followers, And Promoted By Well-Known Artists).